2010
DOI: 10.1182/blood.v116.21.4589.4589
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Transplantation for Relapsed and Refractory Burkitt Lymphoma.

Abstract: 4589 Background: Burkitt lymphoma is a highly aggressive and rapidly proliferating hematologic malignancy. Various chemotherapy regimens (HyperCVAD, CODOX-M/IVAC, REPOCH) have been shown to improve overall survival rate. However, in instances of relapsed or refractory disease, there is no clear-cut standard of care. Hematopoietic stem cell transplantation (HCT) has shown benefit in these patients. Here, we report our institutional experience using HCT for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, 5-year OS was significantly lower in patients with advanced disease (25%). Moreover, in a small cohort of 13 Burkitt lymphoma patients who were treated with HDCT/ABSCT at relapse, Kwon et al [22] reported an encouraging 2-year OS of 75%. Therefore, in the case of chemosensitive relapse, HDCT/ABSCT can be offered as a treatment option, as patients with advanced and chemoresistant disease might benefit from treatment modalities other than HDCT/ABSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 5-year OS was significantly lower in patients with advanced disease (25%). Moreover, in a small cohort of 13 Burkitt lymphoma patients who were treated with HDCT/ABSCT at relapse, Kwon et al [22] reported an encouraging 2-year OS of 75%. Therefore, in the case of chemosensitive relapse, HDCT/ABSCT can be offered as a treatment option, as patients with advanced and chemoresistant disease might benefit from treatment modalities other than HDCT/ABSCT.…”
Section: Discussionmentioning
confidence: 99%